An application based improved round robin CPU scheduling for real time operating system - Mahmud, Nasif; Afrin, Sadiya; Rahman, Fwzana; Monirujjaman, Md. (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.